2009
DOI: 10.1523/jneurosci.0746-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Working Memories of Obstacles Established by Foreleg Stepping in Walking Cats Require Area 5 of the Posterior Parietal Cortex

Abstract: Walking animals rely on working memory to avoid obstacles. One example is the stepping of the hindlegs of quadrupeds over an obstacle. In this case, the obstacle is not visible at the time of hindleg stepping, because of its position between the fore and hindlegs, and working memory must be used to avoid it. We have previously shown that this memory is very precise and surprisingly long-lasting and that it depends on the stepping of the forelegs over the obstacle for its initiation. In this study, we test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 43 publications
(50 reference statements)
3
36
0
Order By: Relevance
“…The PPC may thus have a built-in storage capacity, which requires only periodic updating from visual input. These properties are similar to those of PPC neurons in area 5b that increase their discharge when the obstacle crosses between the forelimbs and hindlimbs, where no direct visual input is available once the obstacle passes under the head of the cat ; see also McVea et al 2009). …”
Section: Role Of Ppc In Control Of Locomotionsupporting
confidence: 56%
“…The PPC may thus have a built-in storage capacity, which requires only periodic updating from visual input. These properties are similar to those of PPC neurons in area 5b that increase their discharge when the obstacle crosses between the forelimbs and hindlimbs, where no direct visual input is available once the obstacle passes under the head of the cat ; see also McVea et al 2009). …”
Section: Role Of Ppc In Control Of Locomotionsupporting
confidence: 56%
“…This is well above the range reported by Schütz and Dürr (Schütz and Dürr, 2011), and hence leaves enough time (on average 141±57ms; A.W., unpublished) for the neuromuscular system to transmit and process the information. However, we cannot exclude the possibility that the time point at which the placement of the foot is actually decided is later, similar to Schütz and Dürr (Schütz and Dürr, 2011), or even earlier, as has been reported for vertebrates that use visual and mechanosensory information to guide leg trajectories during walking [cat (McVea and Pearson, 2007;McVea et al, 2009;Wilkinson and Sherk, 2005), human (Mohagheghi et al, 2004;Patla and Vickers, 2003)]. In the case of humans wanting to place their foot at a specific target position, it has been reported that they fixate on this position on average two steps ahead, and at least 800-1000ms before the limb is placed on the target area (Patla and Vickers, 2003).…”
Section: Targeting Accuracy Changes Between Standing and Moving Targementioning
confidence: 75%
“…This information becomes particularly relevant when navigating through an unknown or irregular terrain. For cats (McVea and Pearson, 2007;McVea et al, 2009;Wilkinson and Sherk, 2005) and humans (Mohagheghi et al, 2004;Patla and Vickers, 2003) it is known that targeting of leg movements is primarily mediated by visual information that is captured on average two steps ahead. Likewise Niven and colleagues showed that locusts visually target their front legs towards the position of a ladder rung and information about the position of the rung is acquired before leg swing is initiated (Niven et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Corticospinal inputs further serve to modify the pattern of spinal locomotor output in situations where there is a need for control of foot placement, such as when there are constraints on the walking pattern 32 or a need to adapt gait to environmental obstacles. 33,34 Activation of red nucleus neurons and the rubrospinal tract coincides with maximal hindimb flexor electromyographical (EMG) activity and is associated with the extent of hip flexion during swing phase. [35][36][37] The lateral vestibular nucleus neurons exhibit high resting discharge rate, which establishes tonic muscle tone of paraspinal muscles extending to the lumbar cord, providing static posture and balance control.…”
Section: Supraspinal Contributionsmentioning
confidence: 99%